Legal Pluralism of the Ammatoa (Ilalang Embaya) Indigenous Community in Marriage Aspects (Analysis Study of Maqasid Al-Shari'ah) - Andi Erni Erna Sari; Abdul Qadir Gassing; Misbahudin Misbahudin (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2022)
This study aims to analyze the legal pluralism of the Ammatoa (Ilalang Embaya) indigenous community in the aspect of marriage. This type of research is qualitative research with a field research approach. The data source comes from primary data obtained from the Kajang tribal chief (Ammatoa), the Kajang tribal community, Kajang tribal community leaders, Kajang tribal traditional leaders, and the Tanah Toa Village Head. Data collection techniques using interviews and observation. The technique to guarantee the validity of the data is the triangulation technique. Data analysis in this study uses Miles Huberman qualitative analysis techniques, namely data reduction (reduction), data presentation (Display), and drawing conclusions (verification). The results of the study can be concluded that 1) there is relevance in the marriage of the Kajang tribal community (Ammatoa) from the stages of finding a mate, application, and marriage procession of the Kajang tribe with the obligation to carry out a traditional procession, fulfill the requirements and laws of marriage as in Islamic law, following the established procedure. stipulated by law, namely registering marriages through KUA by completing files through permits at the local village office, 2) The position of the prohibition of inter-ethnic marriages based on Maqassid Al-Shari'ah is at the dharuriyat level, 3) The law of pairs that stipulates provisions that are not based on instructions from al-Shari'ah. al-Quran and Hadith, then these provisions can be accepted as a rule and then can be followed and obeyed.